Relationship between executive functions and academic performance in psychology students - Cañas Lucendo, Manuel; Roque Herrera, Yosbanys; Fuertes López, Blanca Narcisa (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Executive Functions (EF) (Working Memory, Inhibitory Control, and Cognitive Flexibility) have been associated with Academic Performance (AP). A non-experimental, correlational study was conducted to analyze the predictive relationship between EF and AP in 185 psychology students, selected through a non-probabilistic sampling. The following evaluation applications were utilized: Continuous Attention Test, Visuospatial memory test, Wisconsin Card Sorting Test Variant, Stroop Effect - Colors Game. The results showed a direct positive effect of working memory and inhibitory control and a negative effect of cognitive flexibility on AP. It might be concluded that EF have a low level of prediction on AP.